(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
During the study it has been observed that the most common causative agent for both uncomplicated and complicated UTIs is Escherichia coli which is highly resistant to amphicillin, then followed by klebsiella pneumonia, proteusspp, enterobacterspp, enterococcus spp. the most common gram positive bacteria is staphylococcus aureus. Cystitis (infection of bladder) is common among types of UTI.Out of 100 patients 57(57%) were females and 43(43%) were males. Females are more prone to develop UTI due to physiological changes mostly post-menopause patients. During the study males are mainly associated with enlarge prostate. In the study most common symptoms observed were dysuria or burning micturition, fever and urgency. Magnexforte + sulbactam (34.6%) commonly prescribed antibiotic for both uncomplicated and complicated then followed by cephalosporins, macrolides other class of antibiotics. Fluoroquinolones (5%) class of antibiotic particularly prescribed in case of complicated UTI. It has also been observed that amphicillin and TMP-SMX (trimethoprim-sulfamethoxazole) antibiotics is not recommended because of its resistance